Embracing multiple definitions of learning. Issue 7 (July 2015) - Barron, Andrew B.; Hebets, Eileen A.; Cleland, Thomas A.; Fitzpatrick, Courtney L.; Hauber, Mark E.; Stevens, Jeffrey R.
<x xml:space="preserve">Abstract</x> Definitions of learning vary widely across disciplines, driven largely by different approaches used to assess its occurrence. These definitions can be better reconciled with each other if each is recognized as coherent with a common conceptualization of learning, while appreciating the practical utility of different learning definitions in different contexts.